مقارنة نقد سند الحديث بين أصحاب منهج الوثاقة من الإسلاميين وآراء بعض الحداثيين - الشويلي، حيدر كريم لهمود; رستمي، محمد حسن; رضائي، محمد علي; الزيادي، حيدر جيجان (جامعة البصرة - كلية التربية للعلوم الإنسانية, 2023)
الحديث الشريف هو المصدر التشريعي الثاني بعد القرآن الكريم عند المسلمين، ولذا فقد أولوه اهتماما كبيرا في دراسته وتدارسه، وقد وضعوا مناهج للاستيثاق من الروايات الواردة نظرا للمشكلات العديدة التي رافقت تدوينها. واجه الحديث عددا من الشبهات التي طالته منذ بواكير تدوينه، ولا زالت تثار ضده من فئات عديدة، وأبرزها ما بات يعرف اليوم بالفكر "الحداثي"، وقد جاء هذا البحث لدراسة سند الحديث من وجهة نظر فئة من الإسلاميين وهي الفئة التي اعتمدت السند فقط لقبول أو رد الأخبار، وبين بعض الحداثيين، ونقد كلتا الفئتين. Hadith is the second legislative source after the Holy Quran among Muslims, and therefore, it has received significant attention in its study and examination. They have established methodologies to authenticate the narrations given the numerous issues that accompanied their documentation. Hadith has faced several objections since its inception, and it continues to be challenged by various groups, notably what is now known as 'modernist thought. This research has come to study the chain of narration (isnad) of hadiths from the perspective of a group of Islamists who relied solely on the isnad for accepting or rejecting reports, as well as some modernists, and to critique both groups.
Keywords: التشريع الإسلامي -- القرآن الكريم -- منهج الوثاقة -- أصول الشريعة